A Theoretical Study Of 1, 1-Diphenyl-2-Picrylhydrazyl (Dpph) Radical Scavenging Activities Of Flavonoids Using Electrotopological State Atom (E-State) Parameters - SUPRATIM RAY (International Journal of Pharma and Bio Sciences, 2012)
This study gives a quantitative structure activity relationship (QSAR) correlation of the thirty five flavonoid derivatives having 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activities reported by Seyoum et al. The study was performed using electrotopological state atom (E-state) parameter as descriptors. Stepwise regression analysis was used as a chemometric tool. The predictive ability of the model was judged considering internal (Q2) and external validation (R2pred) (Q2= 0.581, R2pred=0.7284). The developed model indicates the importance of heteroatom oxygen and it is negatively contributed towards activity. Presence of methoxy group in the flavonoid nucleus is detrimental towards activity.